The great heart of the republic : St. Louis and the cultural Civil War - Arenson, Adam, 1978- (Harvard University Press, 2011)
The Civil War Revealed what united as well as what divided Americans in the nineteenth century--not only in its deadly military conflict, but also in the broader battle of ideas, dueling moral systems, and competing national visions that preceded and followed. This cultural civil war was the clash among. North, South, and West, as their leaders sought to shape Manifest Destiny and slavery politics.